ANALISIS FINANSIAL USAHA PERIKANAN TANGKAP DI KELURAHAN NUNUKAN BARAT KABUPATEN NUNUKAN - Muhammad Sahlan; Muhammad Syafril; Eko Sugiharto (2339-1324, 2015)
The purposes of this research were to analyze the feasibility of captured fishery business in Nunukan Barat Village using investment criterias such as NPV, IRR, Net B/C, Payback Period (PbP) and Break Even Point (BEP) based on prices, production and sales levels. Result of the research showed that the capture fishery business was financially feasible to be developed. The value of NPV was Rp. 337.320.897, IRR=382%, Net B/C=15,88, and PbP=3,78 month. The BEP was found above the actual condition of this capture fishery business according to sales, price, and total production measurement.